2010
DOI: 10.3390/s100100901
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Flavors in Carnauba Wax

Abstract: The subject of this study is the development of flavor wax formulations aimed for food and feed products. The melt dispersion technique was applied for the encapsulation of ethyl vanillin in wax microcapsules. The surface morphology of microparticles was investigated using scanning electron microscope (SEM), while the loading content was determined by HPLC measurements. This study shows that the decomposition process under heating proceeds in several steps: vanilla evaporation occurs at around 200 °C, while ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 24 publications
1
56
0
1
Order By: Relevance
“…TGA measurements provide data regarding the thermal stability of F-LM and weight loss during heating 41 . TGA also provides information on the content of volatile components such as water or solvents, ash or filler content and decomposition behavior of the materials 42 .…”
Section: Thermal Analysis Of Materialsmentioning
confidence: 99%
“…TGA measurements provide data regarding the thermal stability of F-LM and weight loss during heating 41 . TGA also provides information on the content of volatile components such as water or solvents, ash or filler content and decomposition behavior of the materials 42 .…”
Section: Thermal Analysis Of Materialsmentioning
confidence: 99%
“…However, carnauba wax has been employed as wall material for vanillin encapsulation by means of a melt dispersion technique [19].…”
Section: Methodsmentioning
confidence: 99%
“…Kayaci and Uyar (2012) produced functional capsules matrix, containing vanillin, having prolonged shelf-life and high temperature stability facilitated by cyclodextrin inclusion complexation. Milanovic et al (2010) showed that the release of ethyl vanillin from wax matrix occurs under heating proceeds at different temperatures; vanillin evaporation occurs close to 200°C, while matrix degradation starts at 250°C. The release of catechins from wax capsules at pH 5 was observed after heating the solution at temperature above 80°C.…”
Section: Edible Coatings As a Stabilizing Matrix For Bioactive Compoundsmentioning
confidence: 99%